تأثير زمن ثابت انقطاع الوصلة الخليوية على أداء الشبكة الخليوية - حسن عباس (Tishreen University, 2019)
This research is an evaluation study of the changing parameter radio link time out and describes the results of the trial by changing parameters of mobile channel such as radio link time out downlink and uplink and the corresponding effect on the performance stats and mobile channel quality. The idea of changing RLINK parameters is to extend the duration of the calls in bad coverage conditions or high interference before losing the call connection. In areas with quality problems and low signal, calls will have more possibilities to avoid a call drop due to bad quality. Parameters RLINKT and RLINKUP were changed from 16 to 24 in PLBSC1, PLBSC2 and OXBSC1. The outcome of the trial showed good results. It has been proved good improvement in traffic drop rate results despite a slight increase in the SQI values. يهدف هذا البحث إلى دراسة مدى تاثير تغييرزمن ثابت انقطاع الاتصال الخليوي على أداء الشبكة الخليوية حيث تصف نتائج القياسات التجريبة على الشبكة الحقيقية مدى تأثير زمن الثابت المطبق في الوصلة الخليوية الصاعدة وفي  الوصلة الهابطة على جودة االاتصال الخليوي  وبارامترات الآداء للشبكة .  وتعتمد فكرة تغيير زمن الثابت لانقطاع الوصلة على تمديد فترة الاتصال ضمن ظروف التغطية الخليوية السيئة أو التداخل القوي للمحطات حيث إنه في مثل هذة الحالات تكون هناك إمكانيات عديدة لتجنب إمكانيات انقطاع الخط بسبب الجودة الرديئة. لقد تم تغيير زمن الثابت للوصلة الصاعدة والهابطة من 16  الى  24 في المقاسم الخليوية PLBSC1 ,PLBSC2,  OXBSC1 لقد أظهرت التجارب العملية نتائج جيدة حيث تم إثبات التحسن  في نسبة انقطاع الخط على الرغم من بعض الرداءة في الجودة.